The art of French Horn Playing - FARKAS, Philip (Summy-Birchard Company, 1956)
1. Choosing the Mouthpiece and hornn2. Care and Maintenance of the Hornn3. Playing Position and use of the right handn4. Fingering and tuningn5. Embouchure